2009
DOI: 10.1002/jcb.22302
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate regulates embryonic endochondral bone development

Abstract: Phosphate is required for terminal differentiation of hypertrophic chondrocytes during postnatal growth plate maturation. In vitro models of chondrocyte differentiation demonstrate that 7mM phosphate, a concentration analogous to that of the late gestational fetus, activates the mitochondrial apoptotic pathway in hypertrophic chondrocytes. This raises the question as to whether extracellular phosphate modulates chondrocyte differentiation and apoptosis during embryonic endochondral bone formation. To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…These results also suggest that the disruption of cellular P i homeostasis causes abnormal endochondral ossification due to a reduction of ATP synthesis in Hyp mice. In support of our study, Zalutskaya et al (32) have recently described that P i activates mitochondrial apoptotic pathways and promotes endochondral ossification.…”
Section: Discussionsupporting
confidence: 91%
“…These results also suggest that the disruption of cellular P i homeostasis causes abnormal endochondral ossification due to a reduction of ATP synthesis in Hyp mice. In support of our study, Zalutskaya et al (32) have recently described that P i activates mitochondrial apoptotic pathways and promotes endochondral ossification.…”
Section: Discussionsupporting
confidence: 91%
“…Hypertrophic chondrocyte apoptosis is first seen at the time of vascular invasion in E14.5 humeri, suggesting that vascular invasion is required for hypertrophic chondrocyte apoptosis (Zalutskaya et al, 2009). Consistent with this hypothesis, the hypertrophic chondrocytes of avascular cultured metatarsals do not undergo apoptosis under normal culture conditions, implicating circulating factors, including phosphate, in the induction of hypertrophic chondrocyte apoptosis in vivo (Zalutskaya et al, 2009). Impaired vascular invasion in the growth plates of c-Raf f/f ; ColII-Cre + mice would be expected to attenuate the exposure of hypertrophic chondrocytes to extracellular phosphate, resulting in a decrease in Erk1/2 phosphorylation and in hypertrophic chondrocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that FGF18 induced chondrocyte hypertrophy and mineralization [42, 43], while FGF9 inhibited terminal differentiation of calvaria-derived cells and mineralization [44, 45]. FGF7 was a potent inhibitor of phosphate transport [46].…”
Section: Discussionmentioning
confidence: 99%